EFL Learners’ Attitude toward Two Major English Varieties: From Perplexity to Prejudice - Rina Herlina; Didih Faridah (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
For EFL learners, English language is a part of the main course to consume at school. However, some of them and even English teachers are not too familiar with 2 major English varieties (EV). They are American English (AE) & British English (BE). So far, that issue doesn’t bring up responsive concern, but some questions from EFL learners prompt such an inquiry. One of those questions is; which one of those EVs has more economical benefit for their future? In addition, frequent debate might occur among EFL learners about the correct version between kid or child, lorry or truck, taxy or cab, flat or apartment and many others. This chaotic mix-up is undeniable. Thus, this study investigates learners’ attitude on both English varieties, BE and AE, in terms of learners’ prejudice and perplexity which are encountered in learning process. This survey embraced 50 university students to put forward their own perspectives on an open-ended questionnaire consisting of four questions. Next, all answers were grouped into three categories to be interpreted. The survey shows that 50% of students insist that AE is the most well-acceptable English across the globe that could contribute to their better future socially and economically, and the rest percentage shows various contradictive arguments. It is suggested that English teachers are supposed to consider the differences between BE and AE in designing teaching material to avoid EFL learners’ perplexity and prejudice on both EVs.